Infrared finite gluon propagator and the structure of chiral symmetry breaking - Montero, J. C. [UNESP]; Natale, A. A. [UNESP]; Rodrigues Da Silva, P. S. [UNESP] (Oxford University Press (OUP), 1996)
We study the chiral symmetry breaking in QCD, using an effective potential for composite operators, with infrared finite gluon propagators that have been found by numerical calculation of the Schwinger-Dyson equations as well as in lattice simulations. The existence of a gluon propagator that is finite at k2 = 0 modifies substantially the transition between the phases with and without chiral symmetry.